Association Between Polypharmacy and Socio-Demographic Factors Among Elderly Residents of Kahrizak Charity Foundation, Tehran, 2010-2011 - Hamid Reza Yavari; Ahmad Ali Akbari Kamrani; Enayatollah Bakhshi; Malihe Saboor; Robab Sahhaf (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: To investigate association between Polypharmacy and socio-demographic factors (including age, sex, education, and smoking) between the elderly residents of Kahrizak Charity Foundation (KCF). Methods & Materials: In a descriptive analytic cross-sectional study, 237 (134 female) elderly residents of KCF, aged 60 and more, included trough randomized cluster sampling, were studied for the number of medications used and the association between polypharmacy (concurrent use of 5 or more medications) and socio-demographic factors, including age, sex, education, and smoking. Results: The mean number of medications used by any resident and the prevalence of polypharmacy were 5.1(±3.22) and 52.3% respectively. Compared with the 60-69 age group, the odds of polypharmacy, insignificantly increased in 70-79 age group (OR=1.09, 95%CI: 0.53-2.25) and decreased in 80 and more age group (OR=0.68, 95%CI: 1.24-0.37). The prevalence and odds of polypharmacy were insignificantly lower in men (OR=0.68, 95% CI 0.37-1.24) and significantly lower in smokers (OR=0.36, 95% CI 0.79-0.17). There was a significant direct association between polypharmacy and more formal education years (OR=1.09, 95%CI: 1.18-1.01). Conclusion: The mean number of medications for any resident and the prevalence of polypharmacy were high in KCF. Increase in years of official education and non-smoking were risk factors of polypharmacy in this population. There was no significant association between age and sex with polypharmacy. The future well-designed national studies among older people living in nursing homes are highly suggested.